Protein translation in mammalian spermatozoa - Nunes, João Cláudio Fonseca (2020)
Reversible protein phosphorylation is the key general mechanism for regulating vital sperm cells functions since sperm cells are highly compartmentalized and almost devoid of transcription and translation. However, there is a small area of uncondensed chromatin where transcription and translation are still possible. There is only one study in the literature showing protein synthesis occurs in spermatozoa during capacitation. The main goal of this work was to study if protein translation occurs, both in human and bovine spermatozoa. In order to achieve that, we monitored protein synthesis using the Surface Sensing of Translation (SUnSET) technique, followed by flow cytometry. The results revealed mRNA translation in spermatozoa. Furthermore, we analysed the impact of translation inhibition by mitochondrial and cytoplasmic ribosomes in the expression levels of diverse spermatozoa proteins. The results show that, while some proteins are affected by translation inhibitors, others remain stable. To conclude, our results support protein synthesis occurs in spermatozoa and show, for the first time, SUnSET technique allows to monitor and quantify the global protein synthesis in mammalian spermatozoa.